1998
DOI: 10.1016/s0927-6505(98)00014-0
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-rays and neutrinos from very young supernova remnants

Abstract: We consider the result of acceleration of heavy ions in the slot gap potential of a very young pulsar with a hot polar cap. Photodisintegration of the heavy ions in the radiation field of the polar cap and pulsar surface gives rise to a flux of energetic neutrons. Some fraction of these neutrons interact with target nuclei in the supernova shell to produce neutrino and gamma-ray signals which should be observable from very young supernova remnants in our galaxy for a range of pulsar parameters.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 47 publications
(62 reference statements)
1
39
0
Order By: Relevance
“…A more specific model for γ-ray and neutrino production in the Crab Nebula has been proposed a few years ago by Bednarek and Protheroe (1997). The general scenario is similar to the one previously discussed for the very young supernova remnants (Protheroe et al 1998): iron nuclei from the Crab pulsar are accelerated in the outer gap (Cheng et al 1986) and photodisintegrate in collisions with the non-thermal radiation field filling the outer gap, thus producing energetic neutrons which are injected into the nebula. Neutrons can decay either inside or outside the Crab nebula.…”
Section: Pulsar Wind Nebulae (Plerions)mentioning
confidence: 79%
See 2 more Smart Citations
“…A more specific model for γ-ray and neutrino production in the Crab Nebula has been proposed a few years ago by Bednarek and Protheroe (1997). The general scenario is similar to the one previously discussed for the very young supernova remnants (Protheroe et al 1998): iron nuclei from the Crab pulsar are accelerated in the outer gap (Cheng et al 1986) and photodisintegrate in collisions with the non-thermal radiation field filling the outer gap, thus producing energetic neutrons which are injected into the nebula. Neutrons can decay either inside or outside the Crab nebula.…”
Section: Pulsar Wind Nebulae (Plerions)mentioning
confidence: 79%
“…Gaisser et al (1989). In this review, we consider more recent models, starting from the one developed by Protheroe et al (1998). In this model the authors suppose that a pulsar with sufficiently short rotational period and high magnetic field has been formed just after the supernova explosion.…”
Section: Supernovae With Energetic Pulsarsmentioning
confidence: 99%
See 1 more Smart Citation
“…As neutrons have a relatively long decay time, ∼ 10 3 γ p s in the observer's frame, they may decay outside the remnant (Protheroe, Bednarek, & Luo 1998). The charged pion decay produces neutrinos, π + → µ + + ν µ → e + + ν e + ν µ + ν µ .…”
Section: Neutrino Flux Predictionmentioning
confidence: 99%
“…In our previous work [17,18], we considered acceleration of iron nuclei in the magnetospheres of very young pulsars, and Crab-type pulsars, in the context of γ-ray and neutrino emission by supernova remnants. We found that, although the photo-disintegration process of iron nuclei during their acceleration and propagation through the neutron star magnetosphere is important, heavy nuclei would be injected into the medium of expanding supernova remnant.…”
Section: Introductionmentioning
confidence: 99%